Developments in oral health care in the Netherlands between 1995 and 2018 - Joost C. L. den Boer; Wil J. M. van der Sanden; Josef J. M. Bruers (BMC, 2020)
Abstract Background Over the past several decades, changes in legislation and regulations have been implemented in oral health care in the Netherlands. In 1995, for example, a major transformation in the funding of oral health care was implemented, after which most oral health care for adults was no longer covered by national insurance. In 1997, the Individual Healthcare Professions Act, in which the authorizations of care providers were described, was established. The Healthcare Quality, Complaints and Disputes Act, established in 2016, concerns the accountability of professional behavior. Regulations concerning employment have changed several times since 1995. These changes have affected the work and practice situation of oral health care providers. Methods Data from many publicly available sources were gathered and combined with internal reports mainly derived from the Data Stations project of the Royal Dutch Dental Association. This project was established in 1995 and, since its initiation, 6716 dentists have participated an average of 6.7 times. Results Between 1995 and 2018, nearly all professional groups in oral health care increased, particularly those of dental hygienists and prevention assistants. The number of dental practices decreased, but practices got larger in terms of dental units, number of patients, and personnel. The percentage of inhabitants visiting oral health care professionals remained unchanged, but the type of care provided moved towards more prevention. Oral health care providers exploited new opportunities to enhance and express their professional behavior. Conclusions Oral health care in the Netherlands has evolved in recent years toward more collaboration in teams, and professions have established institutions to promote the quality and safety of care. Greater emphasis has been placed on prevention of dental diseases. These processes were influenced by new legislation and regulations, demographic changes within professional groups, and other social developments.